For a program of eradication of hepatitis C in the populations at risk (drug users and convicts) - Nava, Felice Alfonso; Alberti, Alfredo; Andreoni, Massimo; Babudieri, Sergio; Barbarini, Giorgio; D'Egidio, Pietro Fausto; Leonardi, Claudio; Lucchini, Alfio (Acta Biomedica Atenei Parmensis, 2018)
Injection drugs are the greater source for HCV infection. About 60% of drug users and about 20-30% of convicts are infected with HCV. HCV infection is often associated with behavioral disorders and drug use. At present, few subjects with HCV belonging to risk groups have been treated with Direct-Acting Antivirals (DAAs). SerDs and prisons should implement the screening for HCV. HCV populations at risk can be successfully treated with DAAs. The primary objective of the linkage to care is the holistic and integrated treatment, and the prevention of reinfections is a priority and essential part of the treatment goals. The removal of the barriers to treatment is a primary goal of the linkage-to-care models and integrated systems; the main action to be undertaken for the linkage to care of the HCV population at risk are screening, referral, treatment and prevention of reinfection. All HCV RNA+ patients may be eligible for treatment, and those with the clinical criteria for starting treatment should be treated with DAAs. All patients should receive a structured harm-reduction program (with skill training). The prevention of the infection is of paramount importance in the linkage to care of the HCV population at risk and is an element which should always be associated with the drug treatment.